Teknik Relaksasi Benson untuk Menurunkan Tekanan Darah Pasien Hipertensi di RSUD Dr. R. Goenteng Taroenadibrata Purbalingga - Aliya Permala Putri; Murniati Murniati; Tri Sumarni (Jurnal Rumpun Ilmu Kesehatan, 2025)
Hypertension is a global health issue with a high prevalence, requiring comprehensive management to prevent complications. Effective nursing interventions are essential in managing this condition, and the Benson relaxation technique has been identified as one of the non-pharmacological approaches to lower blood pressure. This case study aims to describe nursing care for decreased cardiac output in Mrs. M, a patient with hypertension, with a focus on the Benson relaxation technique as an intervention to reduce blood pressure. The research method used is a descriptive case study with a nursing care approach applied to a single patient diagnosed with hypertension. The selected patient is an individual over 18 years of age, diagnosed with stage I to stage II hypertension, has good cognitive abilities to understand instructions, and possesses physical conditions that allow active participation. Nursing care was provided over a period of three days, with the primary intervention being the Benson relaxation technique. Observational results showed a significant decrease in blood pressure: on the first day, the patient's blood pressure was 173/102 mmHg, which decreased to 130/90 mmHg by the third day. The average reduction in blood pressure over the three days was 12 mmHg in systolic and 5.3 mmHg in diastolic pressure. Based on these findings, it can be concluded that the Benson relaxation technique can be implemented as an independent nursing intervention to help reduce blood pressure in hypertensive patients.